Damage Simulation of Cable of Long-Span Concrete Cable-Stayed Bridge. Issue 3 (October 2020) - Zeng, Bin; Zhou, Zhenwei; Wen, Bo; Xu, Qing; Shao, Yanchao; Huang, Liyuan; Wan, Chunfeng
Abstract: Stayed cable is a key part of the force system in terms of cable-stayed bridge, which safety performance can be influenced by damaged cable. In this paper, an effective area method is utilized to simulate the damaged cable. Both the single and double damages are studied, the corresponding cable loss is estimated; and the changes of the mid-span deflection and first-order frequency are discussed. Moreover, the numerical example is carried out by taking the Sutong bridge as the background. The results demonstrat that it is realistic and possible to simulate the cable loss by using the reduced effective area of cable. Furthermore, the deflection of the main span has an evident change when the damaged cable is farther away from pylons; nevertheless, the cable loss has a slight effect on the first-order frequency.